The Assessment of effective implementation OPRAS system in the public service in Tanzania - Msemo, Rehema A (KDI School, 2011)
The government of Tanzania embarked on the implementation of the Open Performance Review and Appraisal System (OPRAS) in the public service with an aim to improve the performance of the public sector on the delivery of its services effectively to the public. Reports have shown that not all the public agencies implemented the performance appraisal system in the way as expected. This study examines critically the OPRA’S implementation process and identifies the procedural and institutional impediments that have arguably been in the way to an effective implementation of the OPRAS system. With the use of several sources of available data I analyze the problem and make recommendation that bring the OPRAS system back on track
Thesis(Master) --KDI School:Master of Public Policy,2011
Keywords: OPRAS (optically pumped reconfigurable antenna system)